1959
DOI: 10.1002/bscb.19590680702
|View full text |Cite
|
Sign up to set email alerts
|

Préparation et Propriétés de Quelques Dérivés de L'hydrazine IV. Sur la Préparation de L'amino‐4 Urazole et de la p‐Urazine

Abstract: The thermal decomposition of phenyl carbazate results in formation of 4-amino urazole. The same compound is formed in reactions which according to other authors yield p-urazine. This six-membered cyclic isomer could not be prepared. The structure of 4-amino urazole is confirmed by study of infrared spectra and its reaction with acetone and benzaldehyde.The reaction of urea with the carbohydrazide has also been studied.Au cours d'une publication antkrieure (I), nous avons signal6 que le carbazinate de phbnyle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Suitable experimental conditions have been developed for a range of 4-aryl- ,, and 4-alkyl-substituted ,,,, urazoles, including polyurazoles derived from aliphatic polyamines (Scheme a). ,,, In the case of 4-(4-alkyl)­phenylurazoles, it should be noted that the yield decreases with increasing carbon number of the alkylaniline, an issue that is not apparent in the case of aliphatic amines . Also, hydrazine can be used as starting material, resulting in the expected 4-aminourazole (Scheme a, R 1 = NH 2 ). …”
Section: Synthesis Of Functionalized Urazole Precursorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Suitable experimental conditions have been developed for a range of 4-aryl- ,, and 4-alkyl-substituted ,,,, urazoles, including polyurazoles derived from aliphatic polyamines (Scheme a). ,,, In the case of 4-(4-alkyl)­phenylurazoles, it should be noted that the yield decreases with increasing carbon number of the alkylaniline, an issue that is not apparent in the case of aliphatic amines . Also, hydrazine can be used as starting material, resulting in the expected 4-aminourazole (Scheme a, R 1 = NH 2 ). …”
Section: Synthesis Of Functionalized Urazole Precursorsmentioning
confidence: 99%
“…However, in most cases this alternative two-step synthesis is not a solution. Efficient examples of this approach are mostly limited to the synthesis of 4-aminourazoles, ,− 4-methylurazoles, , and a few arylurazoles. − , Furdik et al have reported a general synthesis of 4-alkylurazoles in moderate to high yields (52–94%) from 1,6-dialkylbiureas, but the reported yields have been found to be hard to reproduce in later studies. , Relying on similar reactivity, amines have also been directly condensated with 1,2,4-triazolidine-3,5-dione ( 3 ) at elevated temperatures, thus giving the corresponding 4-substituted urazoles (Scheme c). For most substrates, the isolated yield of 4-alkylurazoles in this transimidation approach is lower than in the corresponding amine–biurea condensation–cyclization .…”
Section: Synthesis Of Functionalized Urazole Precursorsmentioning
confidence: 99%
See 2 more Smart Citations